2008
DOI: 10.1080/03079450701774850
|View full text |Cite
|
Sign up to set email alerts
|

Primary chicken tracheal cell culture system for the study of infection with avian respiratory viruses

Abstract: A major route of infection of avian influenza virus (AIV) and Newcastle disease virus (NDV) in chickens is through cells of the respiratory epithelium. Here we describe the development of a method for culture of tracheal epithelial cells from chicken embryos as well as their use in studies of infection with avian respiratory viruses such as low-pathogenicity AIV and lentogenic NDV. Positive immunostaining for cytokeratin, the presence of cilia and microvilli, and microarray analysis of transcribed RNA demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Such receptor specificity can explain the increased infectivity of the H9N2 virus in CTE compared to CEF cells. Similar results on susceptibility of the primary tracheal epithelial chicken cells to infection with H7N3 and H6N1 influenza subtypes have been reported (Zaffuto et al 2008;Shen et al 2011) suggesting that the ciliated cells support the influenza virus growth. However, other host factors such as glycan topology, concentration of invading viruses, local density of receptors, lipid raft microdomains, co-receptors or SA-independent receptors, may also be important determinants of AIV infectivity (Zhang 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Such receptor specificity can explain the increased infectivity of the H9N2 virus in CTE compared to CEF cells. Similar results on susceptibility of the primary tracheal epithelial chicken cells to infection with H7N3 and H6N1 influenza subtypes have been reported (Zaffuto et al 2008;Shen et al 2011) suggesting that the ciliated cells support the influenza virus growth. However, other host factors such as glycan topology, concentration of invading viruses, local density of receptors, lipid raft microdomains, co-receptors or SA-independent receptors, may also be important determinants of AIV infectivity (Zhang 2009).…”
Section: Discussionsupporting
confidence: 81%
“…Lee et al (13) have been suggested that H9N2 viruses belonging to G1 sub-lineage, may be better adapted to the human host and replicates efficiently in human alveolar epithelial cell line (A549) than other H9N2 sub-lineages. Due to the viral tropism, avian influenza viruses reach high titers when grown in chicken-origin cells (14)(15)(16). The efficient replication and infectivity of low pathogenic influenza viruses is achieved in the presence of supplemental trypsin or the type II transmembrane serine proteases (TMPRSS) (14,17).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cell culture can permit study of infection mechanisms under highly controlled conditions, although in vivo systems remain essential for studying responses to disease [23]. Given the demonstration by Petkov et al [24] that a Bu-1-F + and IgM + subpopulation in the bursa is targeted in IBDV infections, the potential of the present agglomerate system for study of NDV infection was examined.…”
Section: Discussionmentioning
confidence: 99%